ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT. ADIRA DINAMIKA MULTI FINANCE TBK CABANG PONTIANAK AHMAD-DAHLAN - B31111031, NOVIAR KHARISMA (Jurnal Manajemen Update, 2016)
PT .Adira Dinamika Multi Finance Tbk is a financial services company engaged in mortgage financing . Company engaged in credit financing to be able to maintain a good reputation in the eyes of its customers . Good service quality and the quality will tend to give more satisfaction to customers who use the services of the company. The purpose of this study was to measure customer satisfaction . The dimensions of service quality that are used to measure customer satisfaction is the dimension of time , the dimensions of cost, quality dimensions , and a moral dimension . The research sample of 100 respondents who are active customers at PT .AdiraDinamika Multi Finance Tbk Branch Pontianak - Ahmad Dahlan . The sampling technique used is Accidental Sampling Method. The analytical tool used multiple linear regression by first tested the validity, reliability and classical assumptions . The results showed that the three dimensionÂ  form of Time Dimension , Dimension Costs and Moral Dimensions is not significant on customer satisfaction, while Quality Dimensions is positive and significant impact on customer satisfaction. Keywords : Quality of Service , Time Dimension , Dimension Cost , Quality Dimensions , Dimension Moral , Customer Satisfaction. Â